Testosterone & gift-giving: Mating confidence moderates the association between digit ratios (2D:4D and rel2) and erotic gift-giving. (March 2016) - Nepomuceno, Marcelo Vinhal; Saad, Gad; Stenstrom, Eric; Mendenhall, Zack; Iglesias, Fabio
Abstract: While prenatal testosterone and estrogen have been associated with various masculinized traits such as risk-taking, aggression, athletic ability, and sex drive, little is known regarding the impact of prenatal hormones on male romantic gift-giving. In a sample of 130 Caucasian men, we investigate the association between digit ratios (2D:4D and rel2 ), a proxy of exposure to prenatal testosterone-to-estrogen ratio, and the likelihood of offering erotic gifts to romantic partners. We hypothesize that men with highly masculinized (low) digit ratios and high mating confidence (i.e., the self-perceived ease with which one gains sexual access to others) will engage in greater erotic gift-giving. We find that masculinized digit ratios are associated with greater erotic gift-giving, but only among men with high mating confidence. Our findings suggest that high prenatal testosterone exposure and high prenatal estrogen exposure are likely to promote a greater desire to offer erotic gifts to a romantic partner, but that only men with high mating confidence have the courage to act on these desires. Highlights: The influence of prenatal testosterone and estrogen on erotic gift-giving is examined. Masculinized (low) 2D:4D and rel2 are associated with greater erotic gift-giving. This association only occurs among men with high mating confidence.